Variable High Order Multiblock Overlapping Grid Methods for Mixed Steady and Unsteady Multiscale Viscous Flows (Communications in Computational Physics, 2018)
Flows containing steady or nearly steady strong shocks on parts of the flowfield, and unsteady turbulence with shocklets on other parts of the flow field aredifficult to capture accurately and efficiently employing the same numerical scheme,even under the multiblock grid or adaptive grid refinement framework. While sixth-order or higher-order shock-capturing methods are appropriate for unsteady turbulence with shocklets, third-order or lower shock-capturing methods are more effectivefor strong steady or nearly steady shocks in terms of convergence. In order to minimize the short comings of low order and high order shock-capturing schemes for thesubject flows, a multiblock overlapping grid with different types of spatial schemesand orders of accuracy on different blocks is proposed. The recently developed singleblock high order filter scheme in generalized geometries for Navier Stokes and magnetohydrodynamics systems is extended to multiblock overlapping grid geometries. Thefirst stage in validating the high order overlapping approach with several test cases isincluded.